Competing Endogenous RNA Network Analysis Reveals Pivotal ceRNAs in Adrenocortical Carcinoma - Liang, Weiwei; Sun, Fangfang (Frontiers in Endocrinology, 2019)
Objective: To construct ceRNA network and identify pivotal competing endogenous RNAs (ceRNAs) in adrenocortical carcinoma (ACC) using ceRNA network analysis. Methods: The RNA sequencing expression data of 77 ACCs in TCGA were obtained from GEPIA. Cancer specific ceRNAs, cancer specific microRNAs (miRNAs), and cancer specific messenger RNAs (mRNAs) were identified. The interaction of cancer specific miRNAs with cancer specific ceRNAs and cancer specific mRNAs were predicted. CeRNA network was constructed and visualized by Cytoscape 3.7.0 software. The genes in ceRNA network regulated GO terms and regulated pathways were performed by function analysis. Survival analysis of pivotal ceRNAs was performed for the pivotal lncRNAs. Result: Twenty-eight cancer specific ceRNAs, 149 cancer specific miRNAs, and 104 mRNAs were identified. CeRNA network was constructed including 10 ceRNAs, 35 miRNAs, and 34 mRNAs. The genes in ceRNA network regulated GO terms and were classified into three groups: cellular component (CC), molecular function (MF), and biological process (BP). The genes in ceRNA network regulated the following pathways: leukocyte transendothelial migration, and proteoglycans in cancer. Survival analysis showed that CTB-63M22.1 and RP1-241P17.4 were significantly associated with ACC patient disease free survival and overall survival. Conclusion: This study has constructed ceRNA networks in ACC. The study provides a set of pivotal ceRNAs for future investigation into the molecular mechanisms.